The effect of arginine vasotocin on courtship behaviour in a blenniid fish with alternative reproductive tactics - Carneiro, Luís Alberto (2012)
In a sex-role reversed population of the peacock blenny, Salaria pavo, two alternative male types are present: (a) older and larger nest-holder males that defend nests in which females come to spawn, and (b) younger and smaller sneaker males that mimic female-courtship behaviour and nuptial colouration in order to try to sneak fertilizations during spawning episodes. In this study the effects of exogenous administration of arginine vasotocin (AVT, 3 μg/g body weight) on the behaviour of nest-holder males, sneakers and females was tested. AVT induced the expression of female courtship behaviour in sneakers and female nuptial colouration in sneakers and in females, but failed to promote the expression of male courtship behaviour in both male types.